2021
DOI: 10.1016/j.joule.2021.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Upstream decarbonization through a carbon takeback obligation: An affordable backstop climate policy

Abstract: In the absence of immediate, rapid, and unprecedented reduction in global demand for carbon-intensive energy and products, the capture and permanent storage of billions of tons of carbon dioxide (CO 2 ) annually will be needed before mid-century to meet Paris Agreement goals. Yet the focus on absolute emission reductions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Discounting makes a large difference in absolute outcomes, but maybe less so in relative outcomes. Diesel comes out worst, without CCS, but policies requiring CCS are possible (Jenkins et al, 2021). Upstream emissions are relatively higher in the BEV case, see their Figures 2, 3 (Pigné et al, 2020).…”
Section: Type 5 Multi Periods and Futures Classic No Time Sequence Mu...mentioning
confidence: 96%
“…Discounting makes a large difference in absolute outcomes, but maybe less so in relative outcomes. Diesel comes out worst, without CCS, but policies requiring CCS are possible (Jenkins et al, 2021). Upstream emissions are relatively higher in the BEV case, see their Figures 2, 3 (Pigné et al, 2020).…”
Section: Type 5 Multi Periods and Futures Classic No Time Sequence Mu...mentioning
confidence: 96%
“…23 In fact, recent studies advocated the near-term emergency deployment of DAC plants even under the current energy supply system to gain knowledge about lowering the operating costs. 24,25 They suggested that large amounts of CO 2 can be removed by DAC, totaling 2.2-2.3, 13-20, and 17-27 Gt year À1 in the years 2050, 2075, and 2100, respectively. It is highly encouraged that the carbon price trajectory is high initially with a moderate rise to avoid excessive carbon removal; but still retaining substantial NET requirements (e.g., 4 Gt year À1 in 2050 and 410 Gt year À1 in 2100).…”
Section: Xuancan Zhu Is An Assistantmentioning
confidence: 99%
“…[2] Some envision other applications such as using carbon to produce materials that effectively "store" the carbon, such as steel replacements [3] (see footnote). 1 The challenge of implementing Extended Producer Responsibility in the oil and gas industry is huge. However, it is not insurmountable.…”
Section: Extended Producer Responsibility In the Oil And Gas Industrymentioning
confidence: 99%